-3=2/3(-1)+x

Simple and best practice solution for -3=2/3(-1)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=2/3(-1)+x equation:



-3=2/3(-1)+x
We move all terms to the left:
-3-(2/3(-1)+x)=0
Domain of the equation: 3(-1)+x)!=0
x∈R
We multiply all the terms by the denominator
-(2-3*3(-1)+x)=0
We calculate terms in parentheses: -(2-3*3(-1)+x), so:
2-3*3(-1)+x
determiningTheFunctionDomain x+2-3*3(-1)
We add all the numbers together, and all the variables
x+11
Back to the equation:
-(x+11)
We get rid of parentheses
-x-11=0
We add all the numbers together, and all the variables
-1x-11=0
We move all terms containing x to the left, all other terms to the right
-x=11
x=11/-1
x=-11

See similar equations:

| 18x+3=15x+2 | | 8(w-4)-4w=-16 | | (5r+20)/15=(4r-24)/4 | | m-6/7=8 | | 12=4+4j | | -11x+10=13x-2 | | 15z^2+23z+4=0 | | n4−2=2 | | 7y-3(y-2)=6(y+1) | | 3/7=y/10 | | 5x+5=-1+x | | 4(3x-9)=-10 | | -1/2(2x-4)=-12 | | n/4−2=2 | | 3(2x+1)+2=1/5-x | | (x-104)=0 | | w/2+5=7 | | w/2+ 5=7 | | 6x+6=3(11-x) | | 7u+8=99 | | q+2/8=6 | | -(5x+8)+5x=4 | | 26-(4-+11)=-5(x+7) | | 7u+8=88 | | 6b=18+4b | | -(6x+6)=-11 | | 7x-7+17(1-x)=-2 | | n-1/2=8 | | P=149P/y | | 2t+5t=t+10 | | z2-144=0 | | m+2/3=6 |

Equations solver categories